Control System Development of Cap-Seal Assembling Machine - Salih Hamoud, Abdullah; Al-Zubaidi, Salah; Sarhan, Samaher Mohammed; Salleh, Mohd Shukor; Mohammed, M. N.; I. Abdullah, Oday (Al-Khwarizmi Engineering Journal, 2024)
The cap-sealing assembling machine is vital in various packaging industrial sectors, particularly the oil sector. The conventional control system of such machines suffers from many demerits, e.g. low productivity, high production cost, high rejection rate, and requires frequent maintenance. Therefore, the current research aims to develop a new control system (N.C.S) based on a programmable logic controller and human-machine interface system (PLSC&HMI). Hence, a fully automated cap-sealing assembling machine can be achieved. The machine is used to produce cap seals for engine oil containers. The performance of the new control system machine is evaluated and compared with the conventional control system (C.C.S) to examine the system feasibility and reliability. The aspects that are subjected to evaluation are the daily working hours (hrs.), glue consumption (Kg), and rejection rate (%). The independent t-test is conducted to deliver a fair comparison and approve the effectiveness of the proposed control system. The obtained findings give the significant development of the proposed control system based on the dependent t-test result. The working hours are reduced to 31.15 hours, and maintenance durations are lowered to the minimum. Also, the N.C.CS reduces the rejection by increasing the accuracy of the finished cap sealed from 88.3 to 99.42 % and consumed glues from 11.5 kg to 7.11 kg.